Gender Differences Between Student–Student Relationship and Cyberbullying Perpetration: An Evolutionary Perspective - Wang, Pengcheng (Journal of interpersonal violence, 2021)
With the development of Internet technology, cyberbullying has become a serious social issue and public concern in modern society. Based on the general aggression model and an evolutionary psychological perspective, the present study aimed to examine (a) whether student–student relationship would be significantly related to cyberbullying, (b) whether materialism would mediate the link between student–student relationship and cyberbullying, (c) whether boys would be more likely to engage in cyberbullying than girls, and (d) whether there would be gender differences among the links between student–student relationship and cyberbullying. The research hypotheses were tested among 712 Chinese middle school students (M age = 13.66 years, SD = 1.36; 50% of the participants were boys) with a moderated mediation model. The results showed that student–student relationship was negatively related to cyberbullying, with their link mediated by materialism. Furthermore, boys were more likely to engage in cyberbullying than girls. Moderated mediation analyses indicated that gender moderated the path between materialism and cyberbullying, with the effect being significant only among the male participants. Gender did not moderate the link between student–student relationship and materialism, and between student–student relationship and cyberbullying. This study highlighted the importance of uncovering the links between adolescents’ offline interpersonal relationships and cyberbullying, as well as the benefits of applying the evolutionary psychological perspective to study cyberbullying.